Blockchain and AI Innovations: Driving Sustainability in Modern Educational Frameworks - Narender, Pramod Rahate (Jurnal Abdimas Peradaban, 2024)
The integration of Blockchain and Artificial Intelligence (AI) technologies is revolutionizing modern educational frameworks, offering innovative solutions that enhance sustainability. This paper explores how Blockchain and AI can drive sustainable practices within education by improving transparency, security, and efficiency in administrative processes, content delivery, and student assessment. Blockchain's decentralized nature ensures the secure storage and verification of academic credentials, reducing fraud and enabling lifelong learning pathways. AI, on the other hand, facilitates personalized learning experiences, optimizing resource allocation and minimizing waste. By analyzing case studies and current implementations of these technologies, this study highlights their potential to create more resilient and adaptable educational systems. The findings suggest that the strategic adoption of Blockchain and AI can significantly contribute to achieving sustainability goals in education, fostering an environment where innovation supports long-term educational development. Recommendations are provided for policymakers and educators to harness these technologies effectively, ensuring that modern education evolves in a sustainable and inclusive manner.